A study of the gross anatomy of posterior communicating artery - Narayanan Sunitha (Wolters Kluwer Medknow Publications, 2017)
Background: The posterior communicating artery is the main collateral channel between internal carotid artery and verteberobasilar system. There are considerable variations in the posterior communicating artery which have both surgical and endovascular implications. Objectives: The present study aims to study the variations of posterior communicating artery such as hypoplasia and absence of the artery. The incidences of the three types of configurations of posterior communicating artery were also noted. Materials and methods: The study was conducted in 60 randomly selected brain specimens fixed in 10% formalin for 10 days in the department of Anatomy. The posterior communicating artery was carefully dissected and observed. Photographs were taken to document the observations. Results: The Posterior Communicating Artery was normal in 13 circles unilaterally [21.7%- Rt. 13% and Lt.9.7%] and bilaterally in 30 circles [50%]. It was hypoplastic in 15% of circles unilaterally and in 10% of circles bilaterally. It was absent in 6.7% of circles unilaterally. Of the three configurations of posterior communicating artery, adult configuration was more common. The other two variant configurations, fetal and transitional were observed in 15% of cases unilaterally. Conclusions: An intact circle of Willis is essential for the stable and constant blood flow to the encephalon. Any changes in its morphology may condition the appearance and the severity of syndromes of vascular insufficiency in adults.